2018
DOI: 10.1111/jocn.14167
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors which promote registered nurses’ intent to stay in emergency and critical care areas

Abstract: To ensure quality care for patients, retention of experienced emergency and critical care nurses is essential to maintaining specialty expertise in these practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Those who experienced good communication, higher motivation, high job security and high job pride were more likely to remain in their job. Similar findings were shown in a study conducted by Van Osch et al () in which participants appreciated being informed about key initiatives and having opportunities to openly share ideas and concerns and, consequently, were more willing to remain working in a critical care setting (Van Osch et al , ). A study of 234 nurses employed in Northeast Florida found six predictors of intent to stay amongst nurses in the acute care setting (Cummings, ).…”
Section: Discussionsupporting
confidence: 82%
“…Those who experienced good communication, higher motivation, high job security and high job pride were more likely to remain in their job. Similar findings were shown in a study conducted by Van Osch et al () in which participants appreciated being informed about key initiatives and having opportunities to openly share ideas and concerns and, consequently, were more willing to remain working in a critical care setting (Van Osch et al , ). A study of 234 nurses employed in Northeast Florida found six predictors of intent to stay amongst nurses in the acute care setting (Cummings, ).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the literature highlights the importance of psychological work environment in predicting turnover [ 27 , 45 , 46 ]. Lack of social support among nurses and phycisians has been shown to be a strong predictor of turnover [ 7 , 13 , 16 , 26 , 47 ]. At the same time, low managerial support appears to favor turnover [ 9 , 14 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurse stress and fatigue levels, as well as emotional exaustion, understaffing and poor patient safety were found to be predictors of nurses intention to leave [6][7][8][9][10][11][12][13][14]. In addition, several studies in different countries highlight the importance of job satisfaction and favorable work environment, with ineffective working relationships with other nurses and physicians and lack of supervisory support increasing turnover intention [7,9,11,[13][14][15][16][17][18]. Burnout, work-life imbalance, moral distress, depression symptoms and workplace violence and bullying appeared to lead to higher nurse turnover intention and had an impact on nurse quality of life [12,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 There are other costs and losses when teams don't collaborate -patients don't receive the care they should receive, resulting in unnecessary impairments, the loss of function and even death 10,11,12 ; there are possibly unnecessary financial costs with waste of health services' precious funds and resources 9 ; and skilled professionals can become burned out and leave healthcare systems. 13,14 There have been calls for collaboration from many health leaders external to our Cameroon setting. For example, the Framework for Action on Interprofessional Education and Collaborative Practice, which was published in 2010 by the World Health Organization, 2 discusses the importance of interprofessional collaboration and identifies the mechanisms that can contribute to collaborative teamwork.…”
Section: Introductionmentioning
confidence: 99%